Metformin may ameliorate inflammatory events of il-18 in some inflammatory conditions - Alzamily, Ajil A; Obaid, Karrar M; Al-Azzawi, Buthainah (Vojenské zdravotnické listy, 2022)
Background: Interleukin-18 (IL-18) belongs to the cytokine family IL-1. IL-18 is synthesized as inactive precursors which need to be processed into an active interleukin by the Caspase-1 enzyme. The role of IL-18 is implicated in several auto-immune disorders, myocardial function, emphysema, metabolic syndromes, psoriasis, bowel inflammation, sepsis, and acute kidney injury. IL-18 exhibits pro-inflammatory properties, such as increased cell adhesion molecules, nitric oxide production, enhancement of T-cell and natural killer cell maturation, and increasing the production of chemokines. This study was designed from November 2020 to February 2021 at Al-Shomali hospital, Babylon governorate, Iraq. This study aimed to assess the levels of IL-18 in patients with PCOS, T2DM and CAD before treatment with metformin and after metformin medication, and to evaluate the roles of IL-18 in the development of this disease. Materials and methods: The study design is a case-control study and patients are selected by simple randomization after diagnosis by a specialist based on clinical diagnosis and laboratory findings. An enzyme-linked immunosorbent test (ELISA) was used to estimate the level of serum IL-18 before and after metformin administration. A total of 300 patients were involved in this study, divided according to their chronic illness as 60 women with PCOS, 60 patients Type 2 diabetes mellitus (T2DM), 60 patients with myocardial infarction (MI), and 60 patients with T2DM and MI. In addition, 30 healthy people as a control group. Results: Before treatment with metformin, the results were exhibited a significant difference (P≤0.0001) in the concentrations of IL-18 in PCOS, T2DM, and patients with CAD as compared with control. While, after metformin treatment, a significant decrease (P≤0. 01, P≤0.0001 and P≤0.001) in IL-18 level in patients with PCOS and T2DM and CAD respectively as compared to before metformin treatment. Conclusion: Metformin administration reduces the inflammatory events of IL-18 in patients with T2DM and CAD and PCOS.
Keywords: interleukin-8; Metformin; Clinical Studies as Topic; zánět; diabetes mellitus; cytokiny; klinická studie jako téma; Diabetes Mellitus; Cytokines; metformin; lidé; Inflammation; Humans; Interleukin-8